Risk Assessment of EPB Shield Construction Based on the Nonlinear FAHP Method - Xueyan Wang; Hang Gong; Qiyu Song; Xiao Yan; Zheng Luo (Advances in Civil Engineering)
There are many risk factors in EPB shield construction. The traditional fuzzy analytic hierarchy process (FAHP) method usually uses a linear analysis method to determine the risk level, but there are often some risk factors with prominent influence, which will reduce the accuracy of the evaluation results. In this paper, a new risk assessment model of Earth pressure balance (EPB) shield construction based on a nonlinear FAHP method is established by introducing nonlinear factors into the comprehensive calculation of the traditional FAHP. First, the new model establishes the framework of EPB shield construction risk analysis based on the work breakdown structure (WBS) and risk breakdown structure (RBS) methods. Then, it constructs an EPB shield construction risk index system by coupling the units of the WBS and RBS. The model constructs a fuzzy consistent judgment matrix, which replaces the 1∼9 scale. Finally, the nonlinear operator is introduced into the FAHP comprehensive calculation, considering the influence of some prominent risk factors, which improves the accuracy of the risk assessment. By applying the new model to the risk analysis of the EPB shield construction section of a tunnel project in Hangzhou, the effectiveness of the model is further verified.